Dr. Franz Heiderichs Österreichische Schulgeographie - Heiderich, Franz; Güttenberger, Heinrich (Verlag Ed. Hölzel, 1930)
Mit einem Abschnitt "Rassen und Völker" (Seite 10-15) und entsprechenden Personenfotografien (Seite 13-14: "Nordische Rasse", "Alpine Rasse", "Nordisch-dinarische Rasse", "Ostrasse", "Dinarische Rasse")